The Immunological Properties of Factor VIII - Uszyński, L (Thrombosis and Haemostasis, 1966)
Rabbits immunized against human AHG fibrinogen-free preparations, were shown to produce anti-AHG antibodies. The inhibitory activity of these antibodies was tested by thromboplastin generation test, thrombelastography, and the specific anti-AHG antibodies neutralization test. The latter test permitted quantitative determination of antigenic form of factor VIII. The inhibitory activity of anti-FI-O-Ta serum resulted exclusively from the anti-AHG antibodies which in coagulation tests behaved like circulating anticoagulants directed against factor VIII.The anti-AHG antibodies were neutralizable by normal human serum or plasma even contained only trace of AHG activity after storage. There was no antigenic form of factor VIII in the severely affected patients with hemophilia A, von Willebrand’s disease nor in the normal plasma adsorbed on bentonite. The presented results suggest a molecular defect of factor VIII in patients with hemophilia A. The severe form of this disease depends, probably, on a major impairment of AHG biosynthesis, leading to changes in the antigenic properties of the molecule. The AHG from rabbit, porcine and bovine plasma respectively did not neutralize the anti-AHG antibodies formed in rabbits immunized against human factor VIII preparations.